Pharmacology of Mikania genus: A Systematic Review - Silva, Andressa Santa Brigida da; Owiti, Alex Oselu; Barbosa, Wagner Luiz Ramos (Pharmacognosy Reviews)
Genus Mikania, in which “guaco” species are included, encloses many species of pharmaceutical interest that are well distributed throughout South America. This work aims to make a systematic review of the clinical and nonclinical data already published about some Mikania species and their existing products, available in the pharmaceutical market. As usual, some species are more studied than others and the most studied species to date are Mikania glomerata, Mikania laevigata, Mikania scandens, and Mikania micrantha. The first two are widely used in Brazil to treat respiratory disorders and are available in different preparations marketed in retail pharmaceutical stores. Among the reported activities, anti‑inflammatory, analgesic, antibacterial, and central nervous system activities were the most tested since they are directly related to the popular use of some species of this genus. In addition, a noteworthy amount of toxicological studies in animals are published in the literature. Thus, this systematic review aims to gather knowledge about Mikania genus and consequently to contribute for a safer use of derivatives of its species.
Keywords: Asteraceae; medicinal plants; pharmacological effects; phytotherapy